The Effect of 3000 K LED Lamps on the Photosynthesis and Morphology of Deciduous Tree Species - Flóra Kolman; Zoltán Kolláth; Péter Molnár; Anna Skribanek (Plant-Environment Interactions)
ABSTRACT The effect of artificial light at night (ALAN) on plants is a less explored area within light pollution research. This is especially true for the physiological parameters of photosynthesis of woody plants. The physiological and morphological values of nineteen deciduous urban tree species illuminated by street lamps with a color temperature of 3000 K were examined for light‐polluted and non‐light‐polluted leaves. The morphological studies covered leaf macromorphology (leaf length, leaf width, and biomass production) and histological development (height of the dorsal epidermis and palisade parenchyma, width of photosynthesizing ground tissue and the leaf). The fluorescence yield of the photochemical system II and the net photosynthesis and transpiration of the leaves exposed to different light conditions were determined in the photosynthetic physiology studies. The species included in the research react differently to artificial light, some are able to utilize the extra lighting at night, while others are negatively affected. In this way, the species can be grouped according to their sensitivity to light pollution. The impact of street lights on vegetation can be easily detected by the combined treatment of micromorphological and photosynthetic physiology tests, macromorphological values are not suitable parameters.